2003
DOI: 10.1038/nature01908
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of novel cooperative swarming in the bacterium Myxococcus xanthus

Abstract: Cooperation among individuals is necessary for evolutionary transitions to higher levels of biological organization. In such transitions, groups of individuals at one level (such as single cells) cooperate to form selective units at a higher level (such as multicellular organisms). Though the evolution of cooperation is difficult to observe directly in higher eukaryotes, microorganisms do offer such an opportunity. Here we report the evolution of novel cooperative behaviour in experimental lineages of the bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
188
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(194 citation statements)
references
References 28 publications
5
188
1
Order By: Relevance
“…Velicer and colleagues (Velicer et al 1998(Velicer et al , 2000Velicer & Stredwick 2002;Fiegna & Velicer 2003;Velicer & Yu 2003) and Strassmann and colleagues (Strassmann et al 2000;Foster et al 2002;Fortunato et al 2003a,b;Queller et al 2003) have shown that cheaters may be common in the bacterium Myxococcus xanthus and in the social amoeba, Dictyostelium discoideum, respectively. In these cases, when the organisms are starved they amass into a non-migrating fruiting body or a slug, respectively, and cheater clones make up a small fraction of stalk-like reproductive structures.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Velicer and colleagues (Velicer et al 1998(Velicer et al , 2000Velicer & Stredwick 2002;Fiegna & Velicer 2003;Velicer & Yu 2003) and Strassmann and colleagues (Strassmann et al 2000;Foster et al 2002;Fortunato et al 2003a,b;Queller et al 2003) have shown that cheaters may be common in the bacterium Myxococcus xanthus and in the social amoeba, Dictyostelium discoideum, respectively. In these cases, when the organisms are starved they amass into a non-migrating fruiting body or a slug, respectively, and cheater clones make up a small fraction of stalk-like reproductive structures.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Rainey & Rainey (2003) found that defecting (cheating) genotypes evolved in populations founded by the cooperating type and were fitter in the presence of this type than in its absence. Moreover, Velicer & Yu (2003) demonstrated that micro-organisms can align their evolutionary interests by evolving primitive forms of cooperation. Our findings indicate that traits which potentially benefit the whole population can and do evolve in other contexts, and that an understanding of such evolution may have implications for medically relevant issues such as antibiotic resistance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These elements exhibit not only spatio-temporal patterns but also collective functions. For instance, the cohort migration of mammalian cells forms tissue patterns (15,16), and the Proteus mirabilis effectively invades human urothelial cells by swarming (17). Further, swarm intelligence has been extensively studied in order to enable a collection of simple robots to perform advanced tasks (18).…”
mentioning
confidence: 99%